The Importance of Culture in Alcohol Care: Listening to First Nations staff in Australian Aboriginal Community Controlled Health Services - Purcell-Khodr, Gemma; Webster, Emma; Harrison, Kristie; Dawson, Angela; Lee, Kim San Kylie; Conigrave, Katherine (The International Indigenous Policy Journal, 2022)
Integration of cultural knowledges and healing practices with Western medical approaches to alcohol care has been reported for residential and community settings. However, there is little evidence on how culture features in alcohol care in primary health settings. We analysed data from semi-structured interviews (from a broader study) with 17 First Nations Australian staff (n=8 men, n=9 women) from 11 Aboriginal and Torres Strait Islander Community Controlled Health Services. We used grounded theory and the 8-ways Aboriginal pedagogy in analysis. We describe three key themes: 1) interpersonal processes; 2) a both-ways approach to healing and alcohol care; and 3) service-wide strategies to achieving both-ways healing. We discuss policy implications of facilitating bicultural alcohol care in primary health settings.